Actividad antiplasmodial y antibacterial in vitro de extractos de la corteza de Erythrina fusca Lour. (Fabaceae) (2016)
ABSTRACT: The phytochemical screening of ethanol extract of the dried bark of Erythrina fusca Lour. (Fabaceae), determined the presence of alkaloids, avonoids, terpenes, and quinones. The chloroform and acetone fractions of ethanol extract of the dried bark of E. fusca, presented a moderate antiplasmodial activity in NF54 and FCB-2 strains of Plasmodium falciparum with IC50 of 12.95, 18.02, 16.60, and 28.36 μg/ml, and a percentages inhibition of maximum average 70.72, 69.74, 87.07, and 85.73%, respectively. The ethanol extract showed inhibition at the concentration of 20 mg/ml for the strain of Staphylococcus aureus and chloroform fraction at the same concentration on Bacillus subtilis, Pseudomona aeruginosa, and Staphylococcus aureus.